Konsep Iḍlāl dalam Tafsir Ibn Kaṡīr - Anis, Ahmad; Al-Qowiy, Ahmad Marjanuddin (Sekolah Tinggi Ilmu Ushuluddin Wadi Mubarak Bogor, 2020)
Prophet Muhammad SAW. in the beginning it was misguided before being given guidance by Allah, the missionary view was a mistake in understanding the nature of iḍlāl. As with an opinion which says that humans do evil because Allah is misled, then Allah has done wrong to his servants. This research is expected to be able to explain the nature of ilāl according to Ibn Kaṡīr and be able to explain the verses of rebuttal to people who misunderstand the nature of ilāl. This research uses the character research model methodology outlined by Dr. Abdul Mustaqim. The results of this study found that: First, the essence of iḍlāl according to Ibn Kaṡīr is that they are misled by Allah not because Allah alone is misleading. Second, rebuttals against people who misunderstand the nature of iḍlāl. In Ibn Kaṡīr's commentary, explaining and interpreting these verses by means of interpretation; 1) tahlili interpretation, 2) bil-Ma'ṡur interpretation. Abstrak Nabi Muhammad saw. pada awalnya adalah sesat sebelum diberi hidayah oleh Allah, pandangan misionaris tersebut adalah sebuah kesalahan dalam memahami tentang hakikat iḍlāl. Seperti halnya sebuah pendapat yang mengatakan bahwa manusia berbuat jahat karena disesatkan Allah, maka Allah telah berbuat zalim kepada hambanya. Penelitian ini diharapkan mampu menjelaskan hakikat iḍlāl menurut Ibn Kaṡīr serta mampu menjelaskan ayat-ayat bantahan terhadap orang yang salah memahami hakikat iḍlāl tersebut. Penelitian ini menggunakan metodologi model penelitian tokoh yang digariskan oleh Dr. Abdul Mustaqim. Hasil penelitian ini menemukan bahwa: Pertama, hakikat iḍlāl menurut Ibn Kaṡīr adalah mereka disesatkan Allah bukan karena Allah semata yang menyesatkan. Kedua, bantahan-bantahan terhadap orang yang salah memahami hakikat iḍlāl. Dalam tafsir Ibn Kaṡīr, menjelaskan dan menafsirkan ayat-ayat tersebut dengan cara penafsiran; 1) tafsir tahlili, 2) tafsir bil-Ma’ṡur.